Oral 2‐oleyl glyceryl ether improves glucose tolerance in mice through the GPR119 receptor. (14th June 2016) - Hassing, H.A.; Engelstoft, M.S.; Sichlau, R.M.; Madsen, A.N.; Rehfeld, J.F.; Pedersen, J.; Jones, R.M.; Holst, J.J.; Schwartz, T.W.; Rosenkilde, M.M.; Hansen, H.S.
Abstract: The intestinal G protein‐coupled receptor GPR119 is a novel metabolic target involving glucagon‐like peptide‐1 (GLP‐1)‐derived insulin‐regulated glucose homeostasis. Endogenous and diet‐derived lipids, including N‐acylethanolamines and 2‐monoacylglycerols (2‐MAG) activate GPR119. The purpose of this work is to evaluate whether 2‐oleoyl glycerol (2‐OG) improves glucose tolerance through GPR119, using wild type (WT) and GPR 119 knock out (KO) mice. We here show that GPR119 is essential for 2‐OG‐mediated release of GLP‐1 and CCK from GLUTag cells, since a GPR119 specific antagonist completely abolished the hormone release. Similarly, in isolated primary colonic crypt cultures from WT mice, GPR119 was required for 2‐OG‐stimulated GLP‐1 release while there was no response in crypts from KO mice. In vivo, gavage with 2‐oleyl glyceryl ether ((2‐OG ether), a stable 2‐OG analog with a potency of 5.3 µM for GPR119 with respect to cAMP formation as compared to 2.3 µM for 2‐OG), significantly (P < 0.05) improved glucose clearance in WT littermates, but not in GPR119 KO mice. Finally, deletion of GPR119 in mice resulted in lower glucagon levels, whereas the levels of insulin and GIP were unchanged. In the present study we show that 2‐OG stimulates GLP‐1 secretion through GPR119 activation in vitro, and that fat‐derived 2‐MAGs are potent candidates for mediating fat‐induced GLP‐1 release through GPR119 in vivo . © 2016 BioFactors, 42(6):665–673, 2016